Did my neurons make me do it? philosophical and neurobiological perspectives on moral responsibility and free will - Murphy, Nancey C. 1951-; Brown, Warren S. (Oxford Univ. Press, 2009)
If humans are purely physical, then must all our thoughts and actions be determined by the laws of neurobiology? Free will, moral responsibility, and reason itself appear to be in jeopardy. But Murphy and Brown present a non-reductive version of physicalism which leaves room for us to be (sometimes) the authors of our own thoughts and actions.
Keywords: Philosophie; Willensfreiheit; Neuropsychologie; Verantwortung